Mencegah Konflik di Aceh Strategi Komunikasi untuk Menjembatani TNI dan Eks Kombatan Gam - Bustami; Hasan Sazali (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
The Aceh conflict was one of the bloodiest conflicts in Indonesia which lasted for 30 years. Even though a peace agreement was signed in 2005, the potential for conflict still exists, especially between the TNI and former GAM fighters. This is caused by several factors such as distrust, past trauma, and lack of effective communication. The aim of this research is to analyze effective communication strategies in preventing conflict in Aceh, especially between the TNI and former GAM fighters. This research uses a qualitative method with a descriptive analytical approach. Data collection was carried out by interviewing various parties, including the TNI, former GAM fighters, community leaders and researchers. The results of this research identified several effective communication strategies for preventing conflict in Aceh, including: First, establishing open and transparent communication between the TNI and former GAM fighters. This can be done through dialogue, regular meetings and joint action. Second, increase mutual understanding and tolerance between the TNI and former GAM fighters. This can be done through education and training on Acehnese culture and history. Third, build trust and mutual respect between the TNI and former GAM fighters. This can be done by showing a commitment to resolving problems peacefully and fairly. Fourth, civil society must be involved in conflict prevention activities. This can be done through community empowerment programs and peaceful conflict resolution. The conclusion of this research is that effective communication is the key to preventing conflict in Aceh. The communication strategy proposed in this research can help build trust and mutual respect between the TNI and former GAM fighters and encourage lasting peace in Aceh.